Angus sire field fertility and in vitro sperm characteristics following use of different sperm insemination doses in Brazilian beef cattle - Menegatti Zoca, Saulo; Shafii, Bahman; Price, William; Utt, Matthew; Harstine, Bo; McDonald, Kristina; Cruppe, Leandro; DeJarnette, Mel; Peters, Lon; Moraes Vasconcelos, Jose Luiz [UNESP]; Dalton, Joseph (Elsevier, 2020)
The primary objective was to determine if Angus bull fertility varied by number of sperm inseminated. A secondary objective was to characterize the potential impact of random variation on fertility using two identical sperm per dose treatments, which differed only in straw color. Computer-assisted sperm analysis (CASA) and flow cytometry (FC) were used to identify post-thaw sperm characteristics associated with field fertility differences between bulls. Ejaculates from five Angus bulls were collected, extended, and cryopreserved at 10, 20, 20 or 40 × 106 sperm per dose in color-coded 0.5-mL French straws. Multiparous cows (n = 4866) from ten Brazilian farms were synchronized for first-service timed artificial insemination (TAI). Bull identification and straw color were recorded at TAI. Pregnancy per TAI (P/TAI) did not differ between sperm doses (43.8, 45.3, 43.8 and 47.1% for 10, 20, 20 or 40 × 106 sperm respectively; P = 0.31) nor was there an interaction between bull and dose (P = 0.53). The P/TAI differed between bulls and ranged from 40.7 to 48.1% (P < 0.01). The overall P/TAI between the two control groups were not different (45.3 vs 43.8%); however, the numerical variation within bull ranged from 0.5 to 4.9 percentage points. Numerous CASA and FC post-thaw sperm characteristics differed among bulls (P < 0.05), but these characteristics did not explain the fertility difference between bulls. Principal component analysis provided a multivariate description of the CASA and FC data, where three principal components (Prin1, Prin2, and Prin3) accounted for a combined total of 88.7% of the data variability. The primary components of each PCA axis were flow cytometric measures of sperm viability and DNA fragmentation (Prin1), and CASA-derived sperm movement patterns (Prin2) and motility (Prin3); however, the relative influence of these characteristics varied by bull. Although fertility differences between bulls were detected, neither sperm per dose nor post-thaw in vitro sperm analyses (CASA and FC) were able to explain the observed differences in field fertility between bulls, further illustrating the difficulties in predicting bull fertility.
Keywords: Beef cattle; Bull fertility; Computer-assisted sperm analysis; Flow cytometry; Sperm dose